2013
DOI: 10.1021/jf401980p
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment and Fractionation of Wheat Straw Using Various Ionic Liquids

Abstract: Pretreatment of lignocellulosic biomass with ionic liquids (ILs) is a promising and challenging process for an alternative method of biomass processing. The present work emphasizes the examination of wheat straw pretreatment using ILs, namely, 1-butyl-3-methylimidazolium hydrogensulfate ([bmim][HSO4]), 1-butyl-3-methylimidazolium thiocyanate ([bmim][SCN]), and 1-butyl-3-methylimidazolium dicyanamide ([bmim][N(CN)2]). Only [bmim][HSO4] was found to achieve a macroscopic complete dissolution of wheat straw durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 53 publications
2
61
1
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19]40 Recently, the ILs containing [HSO 4 ] anion became an appealing option to be used in the biomass pre-treatment, and the acidic properties of this IL allows for the catalytic conversion of biomass. [6][7][8][9][10][11][12][13][14][15][16][17][18][19]40 Recently, the ILs containing [HSO 4 ] anion became an appealing option to be used in the biomass pre-treatment, and the acidic properties of this IL allows for the catalytic conversion of biomass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19]40 Recently, the ILs containing [HSO 4 ] anion became an appealing option to be used in the biomass pre-treatment, and the acidic properties of this IL allows for the catalytic conversion of biomass. [6][7][8][9][10][11][12][13][14][15][16][17][18][19]40 Recently, the ILs containing [HSO 4 ] anion became an appealing option to be used in the biomass pre-treatment, and the acidic properties of this IL allows for the catalytic conversion of biomass.…”
Section: Discussionmentioning
confidence: 99%
“…4 However, to achieve this goal various challenges must be addressed. 5 One of the approaches is the use of more sustainable solvents such as ionic liquids [6][7][8][9][10][11][12][13][14][15][16][17][18][19] and supercritical uids. In addition, the choice of pre-treatment should consider the overall compatibility of feedstocks, enzymes and organisms to be applied, overall economic assessment and environmental impact.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…297 An example is lignocellulosic biomass processing with ILs that allows for the efficient fractionation into main components, such cellulose, hemicellulose, lignin and phenolic compounds. [298][299][300][301][302][303][304] Besides the ability of ILs to dissolve and pre-treat, the solvent power and high selectivity of ILs also allows for the extraction of specific targeted biomolecules from biomass, as demonstrated in literature. 305 In fact, the heterogeneity of food waste generally leads to the disadvantage of adopting multi-step fractionation strategies to obtain target compounds.…”
Section: Green Chemistrymentioning
confidence: 97%
“…In addition, the peak at 1734 cm −1 decreases with increasing [C2mim][O2CH] concentration. Da Costa Lopes et al [60] have suggested that this peak should be assigned to esterlinked acetyl, feruloyl and p-coumaroyl groups between hemicelluloses and lignin. The peak at 1457 cm −1 (lignin and xylan) similarly decreases with increasing [C2mim][O2CH] concentration [54,59,61].…”
Section: Analysis Of Pretreated Biomassmentioning
confidence: 98%